2004
DOI: 10.1111/j.1523-1755.2004.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Two novel ADAMTS13 gene mutations in thrombotic thrombocytopenic purpura/hemolytic-uremic syndrome (TTP/HUS)

Abstract: Enteropathogenic E. coli- and Shiga-like toxin-negative patients who present with hemolytic or thrombocytopenic episodes and HUS like symptoms should be tested for vWF-CP deficiency and other noninfectious reasons for TTP/HUS since plasma substitution possibly provides an efficient therapeutic option for this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 26 publications
1
34
2
1
Order By: Relevance
“…18 Eight different mutations in the first and second CUB domain were reported previously and some were analyzed by in vitro-expression studies, suggesting, consistently with our results, that the CUB domains play a critical role in the biosynthesis and secretion of ADAMTS13. 8,35,36 The 4143_4144insA mutation has been frequently detected in patients with hereditary ADAMTS13 deficiency in northern and central European countries. Schneppenheim and colleagues, after analyzing the segregation of 4143_4144insA mutation using 17 intragenic polymorphic markers in patients and their relatives, suggested that 4143_4144insA is a founder mutation most probably derived from a common ancestor in central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…18 Eight different mutations in the first and second CUB domain were reported previously and some were analyzed by in vitro-expression studies, suggesting, consistently with our results, that the CUB domains play a critical role in the biosynthesis and secretion of ADAMTS13. 8,35,36 The 4143_4144insA mutation has been frequently detected in patients with hereditary ADAMTS13 deficiency in northern and central European countries. Schneppenheim and colleagues, after analyzing the segregation of 4143_4144insA mutation using 17 intragenic polymorphic markers in patients and their relatives, suggested that 4143_4144insA is a founder mutation most probably derived from a common ancestor in central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…27 Of more interest, mutations in the CUB domains result in severe deficiency of plasma ADAMTS13 activity. 9,28,29 In vitro studies have shown that some of the mutants exhibit secretion defect. 30,31 For example, one of the mutations occurs in the second CUB domain, inserts an "A" in between the nucleotides 4143 and 4144 of ADAMTS13 (4143-4144insA), deletes the second CUB domain, and appends REQPG after S1381.…”
Section: Introductionmentioning
confidence: 99%
“…More than forty different mutations of the ADAMTS13 gene have been described (17,58,59,60) and are shown in an extensive table available online (see the Supplemental Material link in the online version of this chapter or at http://www.annualreviews.org). The mutations, which include mis-senses, non-senses, frame-shifting deletions or insertions, and intronic splicing mutations, distribute throughout the various domains of ADAMTS13.…”
Section: Genetic Mutationsmentioning
confidence: 99%